THE ARTISTIC REPRESENTATION OF SOCIAL ISSUES IN CONTEMPORARY UZBEK LITERATURE (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores the ways in which contemporary Uzbek literature reflects and critiques modern social problems through artistic expression. By analyzing works of recent Uzbek writers and poets, the study reveals how themes such as poverty, migration, gender inequality, generational conflict, and the erosion of traditional values are conveyed through narrative structure, character development, symbolism, and dialogue. Literature serves not only as a mirror of society but also as a voice of conscience—questioning injustice and provoking reflection. The article argues that modern Uzbek literature plays a critical role in shaping public discourse and raising awareness of pressing societal concerns through its unique aesthetic language.